(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
During the reproductive stage, uterine fibroids, which are benign smooth muscle tumors, can significantly impact a woman’s quality of life. Pharmacologic treatment and surgical procedures like myomectomy and hysterectomy are included in traditional management. Radiofrequency ablation (RFA) has been a popular minimally invasive method for treating bothersome fibroids in recent years. This study covers RFA’s indications, clinical efficacy, safety profiles, procedural methods, and potential future prospects in the treatment of fibroids. RFA is a good option for women looking for uterine-sparing therapy because of data from recent clinical trials and case series that demonstrate its effectiveness in symptom relief, uterine preservation, and accelerated recovery.